Studi komparasi tingkat kebisingan di lingkungan gedung A dan B UIN malang - Amilia, Ayu Firnanda; Setyowati, Ernaning (Maliki Interdisciplinary Journal, 2024)
A comparative study of noise levels in the Adan B buildings of UIN Maulana Malik Ibrahim Malang was conducted with the aim of analyzing, comparing and providing the best solutions regarding noise levels in buildings A and B. This research was carried out using the field measurement method directly using a sound level meter. Noise measurement is carried out for 24 hours (NGO), which is divided into activities during the day and night. Activities during the day are determined for 16 hours (Ls) in the interval 06.00–22.00. Then at night it is determined for 8 hours (Lm) in the interval 22.00–06.00. The noise level in building A reaches 70dB which is lower than that of building B which reaches 72dB. This is caused by several factors, including the location of building B which is located beside the road and also the main campus field, and the wall material in building A uses a vinyl coating which can reduce noise levels. Apart from vinyl, there are several materials that we recommend including: acoustic tile rohit mouth which can reduce noise levels by 7dB, Acoustic Plaster can reduce noise levels by 4dB, Thick Curtains can reduce noise levels by 5.6dB and concrete blocks which can reduce noise levels by 1, 6dB.